Obesity as a Risk Factor in the Appearance of Haematomas Caused by Low-Molecular-Weight Heparin: A Cross-Sectional Study - Candelaria de la Merced Díaz-González (Nursing Reports, 2023)
Thromboembolic disease (TED) is an important health problem in Europe due to its high morbimortality. Pharmacological prevention is achieved with low-molecular-weight heparin (LMWH), among other strategies, which are supported by a high degree of evidence in the scientific literature. According to its safety data sheet, this injection produces local injuries at a rate of 0.1–1% after administration; however, these percentages are much lower than others reported in several studies focusing on LMWH (44–88%). This high incidence of injuries might be associated with procedural or individual variables. (1) Background: Among the most frequent side effects after the administration of LMWH are pain and haematomas (HMTs), which are influenced by obesity. We aimed to determine the relationship between abdominal skinfold (ASF) value and incidence of HMTs. In addition, I sought to determine how the risk of HMT changed with each mm increase in ASF. (2) Methods: A cross-sectional descriptive study developed in the hospital unit of orthopaedic and trauma surgery was conducted over one year. All participants in the sample were classified based on their ASF and the appearance and area of HMTs were assessed after the administration of enoxaparin. The STROBE checklist was used to evaluate the study. Descriptive statistical analysis and analysis of variance of non-parametric factors were carried out. (3) Results: In a sample of 202 participants (808 Clexane injections), more than 80% presented HMTs. More than 70% of the sample was overweight and more than 50% had an ASF > 36 millimetres (mm). (4) Conclusions: An ASF over 36 mm confers a higher risk of developing HMTs: with each mm increase in the ASF, the risk increases by 4%. Participants who are overweight or obese also present a higher risk of HMT, and these conditions correlate positively with the area of the HMTs. Providing education for the self-administration of the drug after discharge and information about the probability of suffering from local injuries in a more individualised way will lead to fewer primary care nursing consultations, more adherence to the antithrombotic treatment, and, as a consequence, a decrease in TED and health costs.